2009
DOI: 10.1526/003601109789864008
|View full text |Cite
|
Sign up to set email alerts
|

University-Industry Relationships in Colleges of Agriculture and Life Sciences: The Role of Women Faculty

Abstract: An increasing amount of research has been dedicated to studying university-industry relationships (UIRs) . Researchers have studied the impacts of UIRs on the integrity of university research. However, while studies have examined the attitudes and actions of university administration and industry leaders with respect to-UIRs, limited attention has been devoted to the attitudes and actions of women faculty. Drawing on feminist epistemology and academic capitalism research, we develop and test four hypotheses ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A possible overall weaker link to industry of women than men can be seen by relatively fewer agreements, consulting arrangements, and ties to industry that women faculty have in comparison to men faculty at LGIs (Crowe and Goldberger, 2009); however, this same study found the lower number of links to industry by women was not due to an inherent bias of women against industry per se, but primarily due to a lack of women in disciplines that typically have more relationships with industry. For example, they found women represented 52% of nutrition faculty but only 5 and 13% of soil science and agronomy/crop science, respectively (Crowe and Goldberger, 2009).…”
Section: Non-academic Careers In Agricultural Sciencesmentioning
confidence: 69%
See 3 more Smart Citations
“…A possible overall weaker link to industry of women than men can be seen by relatively fewer agreements, consulting arrangements, and ties to industry that women faculty have in comparison to men faculty at LGIs (Crowe and Goldberger, 2009); however, this same study found the lower number of links to industry by women was not due to an inherent bias of women against industry per se, but primarily due to a lack of women in disciplines that typically have more relationships with industry. For example, they found women represented 52% of nutrition faculty but only 5 and 13% of soil science and agronomy/crop science, respectively (Crowe and Goldberger, 2009).…”
Section: Non-academic Careers In Agricultural Sciencesmentioning
confidence: 69%
“…For example, for editorial boards, there is evidence that while there is a general increase of female leadership over time, women still rarely make up more than 20% of these boards (Cho et al, 2014). Crowe and Goldberger (2009) found through surveys of nearly 1000 LGI faculty members that women faculty were less likely (based on Hierarchical Linear Modeling) than their male counterparts to both receive industry support or participate in private consulting for industry. They concluded that this disparity could be due to a scarcity of women entering disciplines within agricultural science that historically and currently have stronger relationships with industry overall, including agronomy and crop science (Crowe and Goldberger, 2009).…”
Section: Gender Representation In Faculty and Leadership At Land Granmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the total female to male ratio in all of AGROSAVIA in 2017 was 0.613, it was only 0.408 in the PG&PGR group surveyed for this study [29]. Several studies focused on gender equality show that the agricultural sciences are a male-dominated field [30,31]. The disciplines of crop sciences, horticulture, and agricultural engineering worldwide have a female-to-male ratio of 0.435, 0.449, and 0.241, respectively [32].…”
Section: The Background and Collaboration Networkmentioning
confidence: 98%